ULSERASI RONGGA MULUT DENGAN LATAR BELAKANG KELAINAN IMUNOLOGIS - Febrina R. Priananto (Faculty of Dentistry, Universitas Indonesia, 2015)
An ulcer is an area of discontinuity of an epithelial surface. Ulceration is the commonest oral soft tissue disorders and very greatly in term of etiology, signs and symptoms, prognosis and treatment. Abnormalities of immune system can cause most oral mucosal ulceration. The purpose of this paper is to discuss the management of some of the more common oral ulcer associated with immunologic disorders. Because the natural history and treatment varies with the diagnosis, the practitioner should becoe familiar with the clinical aspects of the various types of ulcerations so that appropriate treatment can be instituted.